The Development of Innovative Motion Graphics to Raise Environmental Awareness of the Impacts of Wildlife Feeding on Waste Problems in Khao Yai National Park - ศิริปุณย์ ปรัช; สุวรรณมณี ชินาธิป; ณัฏฐากรกิตติ ณัฐณิชา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This creative research aimed to: 1) design and develop motion graphics for a campaign to raise environmental awareness of the impacts of wildlife feeding on waste problems in Khao Yai National Park; 2) examine the effects of the motion graphics in providing knowledge and enhancing awareness of the ecological impacts of wildlife feeding and waste issues; and 3) evaluate the effectiveness of the motion graphics as a learning tool by assessing content quality, design quality, and the satisfaction level of the target audience. The sample consisted of 30 tourists visiting Khao Yai National Park, selected using purposive sampling. The research instruments included the developed motion graphics and evaluation forms for media quality and user satisfaction. The data were analyzed using mean (), percentage, and standard deviation (S.D.). The results indicated that the developed motion graphics were designed using 2D Flat Design combined with Isometric Perspective and Domino Effect storytelling to illustrate the causal relationship between wildlife feeding, ecosystem impacts, and waste problems. The integration of visual design, motion, narration, and sound elements enhanced clarity and effectively communicated the content, leading to increased awareness among viewers. The content quality, as evaluated by content experts, was at a high level (= 4.00, S.D. = 0.46), and the design quality, as evaluated by design experts, was also at a high level (= 4.12, S.D. = 0.75). Furthermore, the satisfaction level of the target audience was at the highest level (= 4.84, S.D. = 0.37). These results indicate that the developed motion graphics are effective and appropriate as a creative communication tool for raising environmental awareness and promoting environmentally responsible behavior among visitors to Khao Yai National Park.